Chemical composition and antifungal activity of oil extracted from leaves turmeric (Curcuma longa) - Rini Yanti; Hermina Nurdiawati; Puji Wulandari; Yudi Pranoto; Muhammad Nur Cahyanto (Hasanuddin University Food Science and Technology Study Program, 2021)
Turmeric rhizomes are commonly used in the culinary, pharmaceutical, herbal medicine, and beverage industries. On the contrary, turmeric leaves are underutilized. The aims of this study were to extract the essential oil from turmeric leaves, characterize the chemical composition of the oil, and determine its antifungal activities against aflatoxin-producing fungi. Steam distillation was used to extract the essential oil from turmeric leaves. The properties of the oil were identified using GC-MS. Antimicrobial activities against Aspergillus flavus and Aspergillus parasiticus were determined. Spores of the fungi were inoculated into potato dextrose agar plates supplemented with various quantities of turmeric leaves essential oil and incubated at 30°C for 7 days. The oil's primary constituents were α-phelandrene(46.70 %), followed by α-terpinolene (17.39 %), 1,8-cineole (8.78 %), benzene (4.24 %), and 2-β pinene (3.64 %). At low (<1%) concentrations, the oil delayed mycelia formation and at high concentrations it significantly inhibit fungal growth (at 1%) and completely inhibit colony formation (at 2%) Additionally, the result show that turmeric leaves oil can inhibited fungus growth at the lowest concentration (0.25 %) when compared to the control over a seven-day incubation period.